Transient high latitude geomagnetic response to rapid increases in solar wind dynamic pressure - Madelaire, Michael; Laundal, Karl M.; Reistad, Jone P.; Hatch, Spencer M.; Ohma, Anders (Frontiers in Astronomy and Space Sciences, 2022)
Rapid changes in solar wind dynamic pressure can produce a transient geomagnetic response in the high latitude ionosphere. In this study we carry out a superposed epoch analysis of the geomagnetic response based on 2058 events. The events are divided into 12 groups based on interplanetary magnetic field clock angle and dipole tilt and the magnetic perturbation field is modeled using spherical harmonics. We find that the high latitude transient current vortices associated with a sudden commencement are most clearly observed when the interplanetary magnetic field is northward during equinox and winter in the northern hemisphere. The high latitude geomagnetic response during northward interplanetary magnetic field is decomposed into a preliminary and main impulse. The preliminary impulse onset is 1--2 minutes prior to the onset of the low/mid latitude geomagnetic response and its rise time is 4--6 minutes. The main impulse onset is around 2 minutes after the low/mid latitude geomagnetic response and has a rise time of 6--11 minutes. When examining the change relative to pre-onset conditions a coherent transient geomagnetic response emerges for all IMF clock and dipole tilt angles. The current vortex associated with the main impulse on the dawnside appears at (9.3$±$0.5 mlt, 64.8$^{°}±$1.5$^{°}$ mlat) and moves westward with a velocity of 5$±$1.4 km/s. The vortex on the duskside appears at (15.3$±$0.9 mlt, 65.8$^{°}±$2.5$^{°}$ mlat) and does not move significantly. In addition, the models were used to recreate the SMR index showing a significant mlt dependence on the magnetic perturbation above 40$^{°}$ mlat and below 10$^{°}$ mlat. The former is thought to be caused by high latitude ionospheric currents. The latter is potentially a combination of the event occurrence probability being skewed toward certain UT ranges for large dipole tilt angles and a UT dependence of the equatorial electrojet magnitude caused by the south atlantic magnetic anomaly.